2011
DOI: 10.1039/c0ee00638f
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon proton conducting polymers for fuel cell catalyst layers

Abstract: Proton exchange membrane fuel cells (PEMFCs) employing proton conducting membranes are promising power sources for automotive applications. Perfluorosulfonic acid (PFSA) ionomer represents the state-of-the-art polymer used in both the membrane and catalyst layer to facilitate the transport of protons. However, PFSA ionomer is recognized as having significant drawbacks for largescale commercialization, which include the high cost of synthesis and use of fluorine-based chemistry. According to published research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
116
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(121 citation statements)
references
References 140 publications
(235 reference statements)
3
116
1
1
Order By: Relevance
“…This is in agreement with other studies of non-PFSA CLs in which electrodes are observed to densify as ionomer loading increases. 5 As a result of densification of the CL, electrode porosity is lost and mass transport resistances increase at high current densities. The particle size of the catalyst ink is observed to increase with 1 loading, with 20 and 30 wt% 1-containing inks being of similar particle size to Nafion-based inks.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in agreement with other studies of non-PFSA CLs in which electrodes are observed to densify as ionomer loading increases. 5 As a result of densification of the CL, electrode porosity is lost and mass transport resistances increase at high current densities. The particle size of the catalyst ink is observed to increase with 1 loading, with 20 and 30 wt% 1-containing inks being of similar particle size to Nafion-based inks.…”
Section: Resultsmentioning
confidence: 99%
“…However, while significant progress has been made studying HC solid polymer electrolytes as membranes, 4 there is very little understanding of their incorporation as ionomer in catalyst layers. 5 Studies on PFSA ionomer-based catalyst layers have revealed the complex nature of the interactions between ionomer, Pt, and the carbon support. [6][7][8] The agglomeration of PFSA ionomer in catalyst inks and during the catalyst layer deposition process are believed to dramatically affect proton, gas and water transport through the catalyst layer.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8 Great advances have been made in recent years in the technological application of these materials for rechargeable batteries, electronic devices, thermal and chemical sensors, biosensors, smart windows etc. [9][10][11][12] An important point that should be considered when choosing a potentially conducting polymer is the ease with which the system can be oxidized or reduced without causing destabilization of the molecule, thereby giving preference to structures that have conjugated unsaturations (low oxidation potential), i.e. π electrons.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27][28] Owing to their highly tunable conductivity, good electrocatalytic activity, and satisfactory electrochemical stability, conducting polymers are considered to be promising electrocatalyst materials for the ORR. [29] Initially, conducting-polymer-based electrodes were fabricated through direct casting of neutral To alleviate the current energy crisis and environmental pollution, sustainable and ecofriendly energy conversion and storage systems are urgently needed. Due to their high conductivity, promising catalytic activity, and excellent electrochemical properties, conducting polymers have been attracting intense attention for use in electrochemical energy conversion and storage.…”
mentioning
confidence: 99%